2021
DOI: 10.1021/acssuschemeng.0c09118
|View full text |Cite
|
Sign up to set email alerts
|

Low-Crystalline Akhtenskite MnO2-Based Aqueous Magnesium-Ion Hybrid Supercapacitors with a Superior Energy Density Boosted by Redox Bromide-Ion Additive Electrolytes

Abstract: Recently, as a new type of hybrid supercapacitors, aqueous magnesium-ion hybrid supercapacitors (MHSs) have triggered continuous attention. Benefiting from the insertion/extraction processes of bivalent magnesium ions in the battery-type electrode, MHS offers the advantage of charging two electrons per ion into the battery-type material. However, the low energy density of reported MHSs is still unsatisfying for their practical applications. Herein, a novel redox bromide-ion additive aqueous MHS (B-MHS) has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 85 publications
0
18
0
Order By: Relevance
“…96 Mg-OMS-1/graphene//CMS capacitor using 0.5 M Mg(NO 3 ) 2 as the electrolyte depicted good electrochemical performance in the voltage window of 0–1.8 V. 79 Han et al reported the design of redox bromide-ion additive aqueous MgICs by introducing the Br 3 − /Br − redox additive in 1 M MgSO 4 . 97 Tian and co-workers developed printable MgICs using MgSO 4 –polyacrylamide (PAM) gel electrolyte. 98 The as-prepared gel electrolyte can return to its initial state after various deformations, such as flattening, bending, and/or stretching.…”
Section: Electrolytes For Nlmicsmentioning
confidence: 99%
“…96 Mg-OMS-1/graphene//CMS capacitor using 0.5 M Mg(NO 3 ) 2 as the electrolyte depicted good electrochemical performance in the voltage window of 0–1.8 V. 79 Han et al reported the design of redox bromide-ion additive aqueous MgICs by introducing the Br 3 − /Br − redox additive in 1 M MgSO 4 . 97 Tian and co-workers developed printable MgICs using MgSO 4 –polyacrylamide (PAM) gel electrolyte. 98 The as-prepared gel electrolyte can return to its initial state after various deformations, such as flattening, bending, and/or stretching.…”
Section: Electrolytes For Nlmicsmentioning
confidence: 99%
“…[14][15][16][17] Most studies on supercapacitors have focused on improving the specific capacity and cycling stability by making full use of the EDLs and pseudocapacitance storage mechanisms. 18,19 EDL charge storage is a very rapid and reversible process, providing high power capability and a stable, long cycle life. However, the relatively small capacity seriously limits the practical application of EDL supercapacitors.…”
Section: Introductionmentioning
confidence: 99%
“…20 Pseudocapacitance can provide additional capacity due to the ion-intercalation/ deintercalation mechanism or interfacial faradic reactions, but the corresponding cycling stability is poor. 7,18,21 Therefore, previous studies have mainly focused on two issues: developing electrode materials with a high specific surface area 20,[22][23][24][25][26][27] and developing electrolyte carriers with better charge transport performance to improve cycling stability and energy storage. [28][29][30][31][32][33][34][35][36] Most of the reported aqueous ion supercapacitors, such as Li + , Na + and Zn 2+ , have low specific capacity, poor cycling performance and dendrite growth.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, sponge-like hierarchical pores on the carbon substrate smooth the transformation of [Fe(CN) 6 ] 3− / [Fe(CN) 6 ] 4− , including the ion diffusion, charge transfer, and ion intercalation/deintercalation, further enhancing the longterm recycling. 34 Following, the Coulombic efficiency η is counted from the formula below:…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Even after 5000 cycles, 89.0% of initial capacitance is still reserved, which demonstrates remarkable the reversibility of the redox couple of [Fe­(CN) 6 ] 3– /[Fe­(CN) 6 ] 4– on the AC-Zn-CP electrode (Figure d). Besides, sponge-like hierarchical pores on the carbon substrate smooth the transformation of [Fe­(CN) 6 ] 3– /[Fe­(CN) 6 ] 4– , including the ion diffusion, charge transfer, and ion intercalation/deintercalation, further enhancing the long-term recycling …”
Section: Resultsmentioning
confidence: 99%